Determinants Of Intention To Use Cash Management System In The Government Agencies With Organization Culture As A Moderating Variable - Aditya Widyastuti; Rosidi Rosidi; Syaiful Iqbal (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The use of Cash Management System (CMS) in government work units is a form of modernisation in the government payment system to improve the efficiency, effectiveness and accountability of government financial management. CMS provides time and cost-efficient benefits and minimizes security risks for financial management but the use of CMS by government work units is not optimal. This study aims to analyze the determinants that influence intention to use CMS, with the variables tested being perceived usefulness, attitude, subjective norms, and trust with organizational culture as moderator variables. The study used SEM PLS to analyze the data by involving 267 samples who were financial management officials at the Ministry of PUPR. The results prove that intention to use CMS is determined by trust, attitude and subjective norms. Perceived usefulness is not proven to affect intention to use CMS and organizational culture is not proven to moderate CMS acceptance. The limitation of the study is that the measurement of organizational culture is limited to the values adopted by the Ministry of PUPR, while organizational culture has broad aspects. Future research can measure organizational culture from different aspects